The Concept of Faith and Its Influence for Social Reform in Qaradawy’s Thought (A study of his book Al-Iman wal Hayah) - Imroatul Istiqomah (Proceeding International Conference on Religion, Science and Education, 2023)
This article investigates what faith is and how it relates to societal transformation. Ibn Taymiyyah, Imam Ghazali, and Said Nursi are only a few of the Muslim academics who have written about this topic in the Islamic tradition. Yusuf Qaradawy, also known as the Global Mufti, is a contemporary scholar who has written extensively about Islamic civilization and social life. This qualitative study aims to interpret the implication of faith in social reforms grounded from Qaradhawi’s legacy: al-Iman wa al-Hayah using an analytical descriptive method. The study’s findings indicate that the essence of faith is a belief that sinks into the heart with full confidence, not mixed with doubts, influencing one’s outlook on life, behavior, and daily actions. This will have a major impact on social change because true faith will foster virtuous behavior, Increasing awareness and affection of other people, animals and the environment, Faith increases productivity and inspires upheaval and rejuvenation.